Video analysis of blows to the head and face at the 1999 World Taekwondo Championships - Roh, J. O.; Watkinson, E. J. (The Journal of Sports Medicine and Physical Fitness, 2002)
BACKGROUND: Limited research has been done on head blows that may result in mild traumatic brain injury in Taekwondo. The purpose of this study was to investigate the fighting conditions under which blows to the head commonly take place, with a view to determining the typical conditions under which injury may occur. METHODS: Experimental design: videotape analysis (retrospective). Setting: the semi-final and final matches (a total of 48 matches) at the 14th World Taekwondo Championships in 1999. Participants: 64 athletes (32 females and 32 males) who won elimination-round matches (out of 563 competitors), aged 15 to 38 years. Measures: frequency, mechanism of head blows, characteristics of situations leading up to and following head blows, frequency of multiple impacts. RESULTS: A total of 35 incidents of head blow occurred (365 blows per 1,000 athlete exposures). All of these head blows were associated with a direct head or face contact and frequently involved: a closed sparring stance, shorter athletes, axe or roundhouse type kicks, attacker's offensive kick, and head-blow-receiver's offensive action with absence of a blocking skill. CONCLUSIONS: To prevent possible brain injury resulting from direct head blows, updated safety education, a complete understanding of concussion for athletes, coaches, and referees, and a rule change in competition Taekwondo are recommended.